Determinants of poorly controlled asthma among asthmatic patients in Jimma University Medical Center, Southwest Ethiopia: a case control study - Zewudie, Ameha (BMC Res Notes, 2019)
OBJECTIVE: The aim of this study was to assess determinants of poorly controlled asthma among asthmatic patients on follow up at Jimma University Medical Center, Southwest Ethiopia. A facility based case control study involving chart review and patient interview was conducted from April 01/2017 to May 30/2017. Consecutive sampling method was used to select 121 cases and 121 controls. Descriptive statistics were used to present socio demographic data and drug prescription pattern while logistic regression was used to identify predictors of poorly controlled asthma. RESULTS: From a total of 242 studied asthmatic patients, 52.9% of controls and 44.6% of cases were males. Poor knowledge about asthma [Adjusted odd ratio(AOR) = 7.30; 95% confidence interval (CI) 1.72–30; P = 0.007], negative attitude about asthma [AOR = 5.10; 95% CI 1.40–18.7; P = 0.014], moderate asthma [AOR = 13.47; 95% CI 2.69–47.23; P = 0.002] and non-adherence to inhaled corticosteroid (ICS) [AOR = 8.52%; 95% CI 2.41–13.45; P = 0.001] were determinants of poorly controlled asthma. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13104-019-4571-y) contains supplementary material, which is available to authorized users.